Performance Analysis of Hybrid Steel-Concrete and Timber-Concrete Composite Pile Systems in Variable Density Sandy Soils Using Experimental and Numerical Insights - Umar, Ibrahim Haruna; Firat, Muge Elif; Lin, Hang; Shehu, Hamza Tijjani; Cao, Rihong (Mdpi, 2025)
Hybrid composite pile foundations face critical challenges in terms of optimizing load transfer mechanisms across variable soil densities, particularly in regions like Kano, Nigeria, characterized by loose to dense sandy deposits and fluctuating groundwater levels. This study addresses the need for sustainable, high-performance foundation systems that are adaptable to diverse geotechnical conditions. The research evaluates the mechanical behavior of steel-concrete and timber-concrete hybrid piles, quantifying skin friction dynamics, combining eight (8) classical ultimate bearing capacity (UBC) methods (Vesic, Hansen, Coyle and Castello, etc.) with numerical simulations, and assessing load distribution across sand relative densities (10%, 35%, 50%, 75%, 95%). Laboratory investigations included the geotechnical characterization of Wudil River well-graded sand (SW), direct shear tests, and interface shear tests on composite materials. Relative densities were calibrated using electro-pneumatic compaction. Increasing Dr from 10% to 95% reduced void ratios (0.886-0.476) and permeability (0.01-0.0001 cm/s) while elevating dry unit weight (14.1-18.0 kN/m3). Skin friction angles rose from 12.8 degrees (steel-concrete) to 37.4 degrees (timber-concrete) at Dr = 95%, with timber interfaces outperforming steel by 7.4 degrees at Dr = 10%. UBC for steel-concrete piles spanned from 353.1 kN (Vesic, Dr = 10%) to 14,379 kN (Vesic, Dr = 95%), while timber-concrete systems achieved 9537.5 kN (Hansen, Dr = 95%). PLAXIS simulations aligned closely with Vesic's predictions (14,202 vs. 14,379 kN). The study underscores the significance of soil density, material interfaces, and method selection in foundation design.
Keywords: hybrid composite piles; ultimate bearing capacity; numerical simulation (PLAXIS 3D); skin friction angle; interface shear test; relative density effects